TANGGAPAN TUJUH KLON TEBU (Saccharum officinarum L.) TERHADAP SERANGAN URET Lepidiota stigma Fabricius - , HAPPY DIAN LESTARI; , Ir. Toekidjo, M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research was conducted to reveal seven clones sugarcane resistance response to white grubs Lepidiota stigma F. on supporting development of high yielding sugarcane. This experimental applied the RAL design. One factor that used in this experimental was seven clones of sugarcane. White grubs L. stigma F. that used in this research is the second instar. The results showed that white grubs L. stigma F. are influence to plant growth and there were the difference in some variable, such as number of leaves, number of tillers, root fresh weight, total fresh weight, root dry weight, total dry weight, root surface area, and root volume. Growth of seven clones of sugarcane for each variable had the different results. Based on 5% DMRT showed that PS 862 is tolerance clone, while BZ 121 is susceptible clone to white grub.